Climate Literacy and Innovations in Climate Change Education: Distance Learning for Sustainable Development - Azeiteiro, Ulisses Miranda; Leal Filho, Walter; Aires, Luísa (Climate Change Management, 2018)
Education for sustainability: Integrating Climate Change and Energy into Lifelong Learning Initiatives for Small Island Developing States -- Distance learning will enable climate refugees to avoid falling into the social risk trap -- Leaving No-one Behind: Improving Climate Change and Entrepreneurship Education in Sub-Saharan Africa through E-Learning and Innovative Governance Systems -- E-learning as tool to feed the world -- Online communities of practice empowering members to realize climate-smart agriculture in developing countries.